Sociodemographic and behavioral characteristics of obese students with sleep problems in Southern Brazil - Rodrigues de LIMA, Tiago; ZANELATTO, Carla; BASTOS, João Luiz; de Assis Guedes de VASCONCELOS, Francisco; Santos SILVA, Diego Augusto (Revista de Nutrição, 2023)
Objective This study estimated the combined prevalence of insuffi cient number of hours of sleep per day and excess body adiposity among young students. The sociodemographic and behavioral characteristics associated with this concurrent health conditions were investigated. Methods This is a cross-sectional school-based study of 975 participants aged 11-14 years in Florianópolis, Santa Catarina state, Brazil. Body adiposity was assessed based on tricipital and subscapular skinfold measurementsand classified according to Lohman. The total number of hours of sleep per day was reported by the students’ parents/guardians, and it was classified as follows: as <8 hours per day and ≥8 hours per day. Data on sociodemographic characteristics, food consumption, and physical activity were collected using a self-administered questionnaire. The chi-square test and multinomial logistic regression with a 5% significance level were used to evaluate the association between the variables. Results The combined prevalence of insufficient number of hours of sleep per day and excess body adiposity was 25.1% (CI95%:20.7-29.9). The sociodemographic and behavioral factors predictive of these conditions were as follows: 13-14 year age group and household monthly income in the intermediate tertile. Conclusion The concurrent presence of insufficient sleep and excess body adiposity was found in a little more than a quarter of the students investigated. The population subgroups belonging to the 13-14 year age group and intermediate tertile of income were more likely to have concurrent insufficient number of hours of sleep per day and excess body adiposity.